2021
DOI: 10.1002/ame2.12194
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid‐induced animal model of kidney disease

Abstract: Kidney disease may be generally classified clinically into two categories: acute kidney injury (AKI) and chronic kidney disease (CKD), both of which are tightly interconnected. 1-3 AKI can often develop in clinical settings in critically ill patients, leading to increased morbidity and mortality. 4,5 AKI is manifested by a rapid decline in the glomerular filtration rates (GFRs) 6 and its pathogenesis is complex, involving ischemia, sepsis, drug toxicity, and trauma. 7 If left unmanaged, AKI can develop into CK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 245 publications
(252 reference statements)
2
34
0
Order By: Relevance
“…Male mice (8 to 10 weeks old) weighing 20 to 25 g were used in the study. The mice were administered an intraperitoneal injection of folic acid (FA, 250 mg/kg dose) (Sigma) dissolved in NaHCO 3 [ 22 , 23 , 24 ]. The control mice were administered an intraperitoneal injection of vehicle (0.3 mol/L NaHCO 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Male mice (8 to 10 weeks old) weighing 20 to 25 g were used in the study. The mice were administered an intraperitoneal injection of folic acid (FA, 250 mg/kg dose) (Sigma) dissolved in NaHCO 3 [ 22 , 23 , 24 ]. The control mice were administered an intraperitoneal injection of vehicle (0.3 mol/L NaHCO 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that single or multiple injections of high-dose folic acid (125–250 mg/kg BW) caused tubular necrosis, oxidative stress and increased creatinine levels in rodents [ 52 , 53 , 54 ]. On the other hand, low-dose folic acid had beneficial effects on the cardiovascular system, and improved hyperhomocysteinemia and diabetes [ 23 , 45 , 55 , 56 ]. The 5-MTHF is biologically active and is the primary form of folate in systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, numerous diabetic kidney injury biomarkers, such as those recently reported by Pelle et al [ 46 ] and Natesan et al [ 11 ], have also not been systematically and comprehensively evaluated in this NA-STZ animal model. Most studies use popular kidney injury parameters [ 47 ] such as blood urea nitrogen (BUN), serum cystatin C, creatinine, uric acid, or/and estimated glomerular flow rate (eGFR) for the evaluation of diabetic kidney injury after NA-STZ injections. The histopathological staining of kidney is also frequently used for the analysis of kidney injury in this NA-STZ animal model.…”
Section: Renal Pathophysiology In This Na/stz Animal Modelmentioning
confidence: 99%
“…Additionally, this model could also provide a platform for testing the therapeutic effects of stem cells and gene therapy on DN [ 11 ]. For studying multiple kidney disease-causing risk factors, this model could also be combined with other kidney disease animal models, such as those induced by folic acid [ 47 , 124 , 125 , 126 ], cisplatin [ 127 , 128 ], cadmium [ 129 , 130 , 131 ], lipopolysaccharide [ 132 , 133 ], and hypoxia or ischemia reperfusion [ 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ].…”
Section: Redox-related Mechanisms That Remain To Be Elucidated In Thi...mentioning
confidence: 99%